Temporal Trends of In-Hospital Mortality in Patients Treated with Intra-Aortic Balloon Pumping: A Nationwide Population Study in Taiwan, 1998-2008 - Ho, Chung-Han (PLoS One, 2015)
Intra-aortic balloon pumping (IABP) is widely used for hemodynamic support in critical patients with cardiogenic shock (CS). We examined whether the in-hospital mortality of patients in Taiwan treated with IABP has recently declined. We used Taiwan’s National Health Insurance Research Database to retrospectively review the in-hospital all-cause mortality of 9952 (7146 men [71.8%]) 18-year-old and older patients treated with IABP between 1998 and 2008. The mortality rate was 13.84% (n = 1377). The urbanization levels of the hospitals, and the number of days in the intensive care unit, of hospitalization, and of IABP treatment, and prior percutaneous coronary intervention (PCI) were associated with mortality. Seven thousand six hundred thirty-five patients (76.72%) underwent coronary artery bypass grafting (CABG) surgery, and 576 (5.79%) underwent high-risk PCI with IABP treatment. The number of patients treated with IABP significantly increased during this decade (p(trend) < 0.0001), the in-hospital all-cause mortality for patients treated with IABP significantly decreased (p(trend) = 0.0243), but the in-hospital all-cause mortality of patients who underwent CABG and PCI plus IABP did not decrease. In conclusion, the in-hospital mortality rate of IABP treatment decreased annually in Taiwan during the study period. However, high-risk patients who underwent coronary revascularization with IABP had a higher and unstable in-hospital mortality rate.